CARDIOVASCULAR RISK ASSESSMENT IN PATIENTS ON HEMODIALYSIS IN SULAIMANI CITY - Mohammed, Mohammed O.; Gharib, Kalthum M; Gharib, Soran M. (Journal of Sulaimani Medical College, 2020)
Background Cardiovascular disease is the major cause of morbidity and mortality in patients with end-stage renal disease on hemodialysis. Cardiovascular disease is a group of disorders of the heart and the blood vessels. The end-stage renal disease required dialysis. Currently, Sulaimani city, has approximately 400 patients on hemodialysis. Objectives To determine the level of cardiovascular disease risk factors according to the World Health Organization / International Society of hypertension risk prediction charts to assess cardiovascular disease risk factors among patients with end-stage renal disease on hemodialysis. Patients and Methods This study is quantitative design (descriptive, cross-sectional) study, which was performed in two dialysis centers in Sulaimani City; those are the dialysis department-Shar teaching hospital and the dialysis center in Qrga. From September 2018 to March 2019, one hundred end-stages renal disease patients on hemodialysis were recruited. The socio-demographic, history and risks of cardiovascular disease, vital signs, anthropometric measurements, and laboratory investigations, were analyzed. Statistical Package for Social Sciences version (24) (SPSS) was used, the data analyzed was performed through; Descriptive statistics (frequency, percentage, mean, standard deviation, minimum, maximum and range). Inferential statistics (correlation test, chi-square, p-value, Fisher Exact Test). Results The mean age of the participants was 55.6 ±14.4 years. (53%) female (47%) male. Total cardiovascular disease risk levels were; (75%) low risk, (10%) moderate risk, (6%) high risk (9%) very high risk. Risk factors of cardiovascular disease were; hypertension (89%), diabetes mellitus (38%), smoker (27%), alcoholic (8%). Laboratory parameters; cholesterol of (8%) was more than 200mg/dl, Triglyceride of (14%) was more than 150 mg/dl. There was significant association between different CVD risk levels and some variables; age (p=0.016), SBP (p=<0.001) and respiratory rate (p=0.039) with CVD risk levels. Conclusion Most of the participants were married, female, illiterate, urban residence, and were on hemodialysis less than 1-year duration. A significant association between cardiovascular disease risks and each of Age, occupation, diabetes mellitus, history of ischemic heart disease, Systolic blood pressure, Diastolic blood pressure, pulse rate, respiratory rate, and 2 hr. postprandial blood glucose.
Keywords: Cardiovascular disease risk factors; End-stage renal disease; Hemodialysis; Sulaimani city